Picture-Cued Sequence Task: How Does It Effect to Students’ English Writing Ability? - Lala Septyaningrum; Wiyaka Wiyaka; Entika Fani Prastikawati (LPPM Universitas PGRI Semarang, 2024)
The research aimed to find out the effect of picture-cued sequence tasks (PCST) in improving students’ writing ability and the students’ perspectives on the use of PCST in writing. This research carried out quantitative method and quasi experimental design, conducted by using pre-test, treatment, and post- test. The researchers also gave the closed questionnaire to the class who were taught by using PCST. The population was the 8th students of SMP N 6 Semarang in the academic year 2024/2025. The samples were 8F as a control group and 8H as an experimental group. The control group was taught without using PCST; however, the experimental group was taught by using PCST. The data was collected by giving the writing test about recount text and closed questionnaire to 8H class. The researchers analyzed the collected data by using a t-test. The result of data analysis showed that the value of t-count higher than t-table (9.976>2.042) at the level of significant of a 0,025 and degree of freedom is 31. It means that the (Ha) was accepted and (Ho) was rejected. To add, the result of closed questionnaire also proved that the use of PCST have an effectiveness in improving students’ writing ability.